A mixed-methods study of tailor-made animated cartoons in teaching punctuation in EFL writing. Issue 1 (12th September 2018) - Bakla, Arif
Abstract: Despite their potential benefits, teacher-created animated cartoons have not found much room in second-language (L2) research, probably due to some technical challenges involved in creating them. This paper reports the findings of a mixed-methods embedded experimental study, designed to test the impact of tailor-made animated cartoons on the correct use of common punctuation rules in English. The participants were 112 Turkish-first language (L1) learners of English, assigned to either the treatment or control group through random cluster sampling. The instructional materials in the treatment group included teacher-created animated cartoons, exercises designed using SCORM-compliant software, and a forum for discussions in Moodle. The participants in the control group, on the other hand, used PowerPoint presentations (PPTs) instead of animated cartoons and completed the same follow-up activities. Quantitative results suggested that the treatment and control groups' post-test and late post-test scores significantly differed in favour of the former. Moreover, qualitative data from semi-structured interviews and document analysis revealed that the participants, especially those in the treatment group, viewed this learning experience highly positively. The findings globally imply that tailor-made animated cartoons might facilitate the learning of punctuation and help raise students' awareness of it.